PENGARUH POROSITAS TANAH DAN PERSENTASE LUAS LAHAN TERHADAP KOEFISIEN ALIRAN PERMUKAAN - Didik Setiawan; Bambang Surendro; Muhammad Amin (Wahana Ilmuwan, 2017)
The extent of a region of the earth's surface in the form of land and forest area with the increase of population, will change the land use as a form of human needs itself, one of which is the expansion of settlements is accompanied by covered of pavement, then the soil is able to function to absorb the water will be the region watertight, so that the necessary reference to the use of land for the balance of the environment is maintained. The purpose of this study was to determine the effect of porosity value and proportion of the value of the land area of the surface flow coefficient (C). This research was conducted using a model catchment area measurements conducted that measure the value of soil porosity, soil density, intensity of average rainfall, runoff volume, and flow coefficient (C). The slope of the land used is 2%. variable percentage of land area (PLA) in this research is 20%, 30% and 10% forest, 40%, 50% and 10% forest and 60%. The results showed that the highest value of C variable PLA 60% with coefficient 0,687. On the value of soil porosity (n) 16% C values of 0.300, while the porosity of the soil (n) 20% of the value of C 0.264 and the value of soil porosity (n) 35% gain with a value of C 0.129. ANOVA test results showed that the soil porosity and percentage of land area (PLA) positive and significant impact on the flow coefficient (C).